Analisis Konversi Lahan Sawah Menjadi Kawasan Permukiman di Kota Pariaman - Fikri, Rahmawati (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
This study aims to determine 1) the area of ​​rice fields converted into settlements in Pariaman City in 2002-2020. 2) the process of converting paddy fields into residential areas in 2002-2020 in Pariaman City. 3) factors causing changes in the function of paddy fields into residential areas in Pariaman City. The research method used is sequential explanatory designs, which combines quantitative and qualitative research methods sequentially. The data used in this study is secondary data in the form of Landsat 7+ETM and Landsat 8+ETM images as well as data from interviews with sources in Pariaman City. The results of the study were 1) the area of ​​rice fields in Pariaman City from 2002-2020 decreased to 993.7 hectares, while the increase in settlement area reached 1825 hectares. 2) the conversion process occurs due to the increasing population, land value, inheritance system, housing developers, and infrastructure needs. 3) the factors that cause land conversion in Pariaman City are external factors, namely the dynamics of urban growth (physical and spatial), demographic and economic, and internal factors caused by the socio-economic conditions of agricultural households using land.